Properties of tofu coagulated with Cardoon flower (Cynara Cardunculus L.) (Research, Society and Development, 2021)
Tofu was elaborated using water-soluble extract of soybean grains from the cultivar BRS 267 with cardoon flower (C. Cardunculus L.), as coagulant as an alternative to the traditional coagulant magnesium chloride. The tofu were evaluated in relation to physical, chemical, microbiological and sensory properties during 14 days. Was obsersed for the tofu coagulated with cardoon flower that the moisture, pH, total mineral, protein, and syneresis decreased with the storage, while Kunitz Trypsin Inhibitor, ureatic activity and phytic acid did not change. It was also obtained a positive effect for color (L*, a*) parameters, phytic acid, yield, syneresis, and acceptance. The textural properties, showed a tendency to increase of hardness and stickiness, while springiness and cohesiveness decreased during storage. Structurally, presented irregular-shaped, small pores or cavities. The sensory analysis, showed has great acceptance and purchase intent. Then, the cardoon flower can be used as vegetal coagulant improving the quality properties of tofu, in relation to magnesium chloride.